2003
DOI: 10.1186/1471-2091-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Methodological factors influencing measurement and processing of plasma reelin in humans

Abstract: BackgroundReelin, intensively studied as an extracellular protein that regulates brain development, is also expressed in a variety of tissues and a circulating pool of reelin exists in adult mammals. Here we describe the methodological and biological foundation for carrying out and interpreting clinical studies of plasma reelin.ResultsReelin in human plasma was sensitive to proteolysis, freeze-thawing and heating during long-term storage, sample preparation and electrophoresis. Reelin in plasma was a dimer und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 39 publications
5
29
0
Order By: Relevance
“…Here we report consistent evidence not only of increased Reelin levels in CSF and affected brain areas of AD patients but also of increased transcriptional activity of the Reelin gene. Moreover, our data show that CSF storage and heating conditions are key factors in determining Reelin protein levels, in agreement with another study (24). Our covariance analyses further show that these differences are not attributable to age or gender (see Supporting Text and Table 1, which are published as supporting information on the PNAS web site).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Here we report consistent evidence not only of increased Reelin levels in CSF and affected brain areas of AD patients but also of increased transcriptional activity of the Reelin gene. Moreover, our data show that CSF storage and heating conditions are key factors in determining Reelin protein levels, in agreement with another study (24). Our covariance analyses further show that these differences are not attributable to age or gender (see Supporting Text and Table 1, which are published as supporting information on the PNAS web site).…”
Section: Discussionsupporting
confidence: 91%
“…7, which is published as supporting information on the PNAS web site). Similar to previous reports (13,24), the relative abundance of Reelin bands differed in plasma and CSF. Neither the intensity of the individual bands nor their relative banding pattern was altered in plasma from AD and mild cognitive impairment patients compared with NDC cases.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…It is known that reelin forms a covalent dimer via intermolecular disulfide bond(s) (16,22). In the present study, we determined the critical cysteine residue participating in the formation of the covalent dimer and showed that the dimer formation via this cysteine residue is required for the full biological activity of reelin.…”
Section: Discussionmentioning
confidence: 85%
“…Disulfide-linked oligomers have been detected in cell culture supernatant from 293T cells transiently transfected with full-length reelin, in the embryonic brain homogenates prepared from the cerebral cortex, and in human plasma (16,22). However, neither the number of reelin protomers contained in the functional oligomer nor the Cys residue(s) responsible for the cross-linking has been determined.…”
mentioning
confidence: 99%